2019
DOI: 10.1530/rep-18-0456
|View full text |Cite
|
Sign up to set email alerts
|

Tri-ortho-cresyl phosphate induces autophagy of mouse ovarian granulosa cells

Abstract: Tri-ortho-cresyl phosphate (TOCP) has been widely used as plasticizers, plastic softeners and flame-retardants in industry and reported to have male reproductive toxicology. However, it is still unknown whether TOCP affects the female reproductive system and its underlying mechanism. In the present study, we found that TOCP exposure significantly decreased ovarian coefficient, caused disintegration and depletion of the granulosa cells in the ovary tissue and significantly inhibited the level of serum estradiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…We also found that TOCP could induce autophagy of mouse spermatogonial stem cells and mouse Leydig TM3 cells . In the present study, we found that TOCP exposure induced autophagic cell death of mouse ovarian granulosa cells, which was in accordance with our previous results . The SQSTM1/p62 protein serves as a link between LC3 and ubiquitinated substrates.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We also found that TOCP could induce autophagy of mouse spermatogonial stem cells and mouse Leydig TM3 cells . In the present study, we found that TOCP exposure induced autophagic cell death of mouse ovarian granulosa cells, which was in accordance with our previous results . The SQSTM1/p62 protein serves as a link between LC3 and ubiquitinated substrates.…”
Section: Discussionsupporting
confidence: 93%
“…We also discovered that TOCP could reduce sperm density in epididymis and inhibit viability of spermatogonial stem cells in mice and even inhibit viability of mouse Leydig TM3 cells . TOCP has also been reported to cause ovarian failure and decrease serum estradiol concentration . One of the important function of ovarian granulosa cells is to synthesize and secrete estradiol, which indicates that TOCP could cause ovarian granulosa cells damage.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations